2021
DOI: 10.1177/17588359211000593
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of ribociclib plus letrozoleversuspalbociclib plus letrozole or letrozole as monotherapy in first-line treatment of postmenopausal women with HR+/HER2− locally advanced or metastatic breast cancer: a Brazilian private payer perspective

Abstract: Background: The global burden of breast cancer (BC) is high, especially in advanced stages. CDK 4/6 inhibitors represent a paradigm shift in the treatment of advanced BC HR+/HER2−, given the clinically and statistically significant gain in overall survival associated with this new class of medications. Nevertheless, as an innovation, the incorporation of these drugs impacts healthcare budgets, requiring cost-effectiveness analyses for decision-making. The aim of this study was to evaluate the cost-effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Ribociclib was more cost-effective than abemaciclib and palbociclib for postmenopausal women with HR+/HER2– advanced breast cancer in Brazil. 48,49 In Mexico, only abemaciclib was found to be cost-effective among CDK4/6 inhibitors for HR+/HER2– advanced breast cancer. 50 A recent study found the addition of ribociclib or palbociclib to fulvestrant for HR+/HER2– metastatic breast cancer to be cost-ineffective in India.…”
Section: Discussionmentioning
confidence: 99%
“…Ribociclib was more cost-effective than abemaciclib and palbociclib for postmenopausal women with HR+/HER2– advanced breast cancer in Brazil. 48,49 In Mexico, only abemaciclib was found to be cost-effective among CDK4/6 inhibitors for HR+/HER2– advanced breast cancer. 50 A recent study found the addition of ribociclib or palbociclib to fulvestrant for HR+/HER2– metastatic breast cancer to be cost-ineffective in India.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that in HR+ BC patients, the downstream HR signaling pathway in tumor tissue of PPBC patients was more similar to the pathway of HR negative BC patients ( 37 , 38 ). Therefore, further studies should be conducted to identify potential therapeutic strategies for PPBC by combining existing efficacy evaluations and outcome data, and to determine whether existing agents, such as CDK4/6 inhibitors, can reverse resistance to HR+ PPBC endocrine therapy ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, cyclin-dependent kinase (CDK) 4/6 inhibitors have come into widespread use in the treatment of HR+/HER2− BC patients ( 12 ). CDK4/6 inhibitors represent a paradigm shift in the treatment of advanced BC HR+/HER2−, given the clinically and statistically significant gain in overall survival associated with this new class of medications ( 13 ). However, the report on the application and efficacy of CDK4/6 inhibitors in HR+ PPBC patients is still blank.…”
Section: Introductionmentioning
confidence: 99%
“…ANS also uses HTA for incorporation decisions, and cost-effectiveness studies conducted from the perspective of the private health care system were an important criterion in that decision-making. 29 Providing access to these innovations only for patients in the private health care system will exacerbate the differences between both health care systems, thus increasing inequity in BC treatment. Lack of access to CDK4/6 inhibitors in the public setting represents an important gap to be filled, considering the recognized importance of benefits to patients with BC.…”
Section: Discussionmentioning
confidence: 99%